Untersuchungen zum Verlauf von Progesteron, freien und konjugierten Östrogenen sowie von Relaxin im peripheren Blut von Norwegischen Waldkatzen im Verlauf der Trächtigkeit und der Pseudogravidität - Dreker, Christian; Justus Liebig University Giessen (My University, 2003)
In zeitlich gestaffelt entnommenen Blutproben sechs gravider und sechs pseudogravider Norwegischer Waldkatzen wurde der Verlauf von Progesteron, Östrogenen und Relaxin mittels radioimmunologischer Verfahren bestimmt. Estradiol 17ß, Estradiol 17 alpha sowie Estron konnten quantitativ und qualitativ während der Trächtigkeit und der Pseudogravidität gleichermaßen nachgewiesen werden. Die Unterschiede hinsichtlich des Auftretens von Progesteron während der Trächtigkeit und der Pseudogravidität waren hochsignifikant. Relaxin war ausschließlich bei den graviden Tieren ab dem 25. Tag der Trächtigkeit nachzuweisen. Diese Beobachtungen bestätigen die in der Literatur gemachten Angaben und lassen im Hinblick auf die endokrine Regulation der Gravidität und der Pseudogravidität auf keine besondere Situation bei der Norwegischen Waldkatze schließen.

The concentrations of oestrogens, as well of progesterone and relaxin were determined in blood samples of six pregnant and six pseudopregnant Norwegian Forest Cats using established radioimmunoassay procedures. Distinction between free and conjugated oestrogens was by means of enzyme hydrolysis and selective extraction, separate measurement of E1, E2a and E2beta was restricted to the pooled plasma samples and achieved by high performance liquid chromatography. Qualitative and quantitative measurement of all three oestrogens was possible with the conjugated forms exceeding the free forms by the factor 1.4 to 4.2. No differences in the occurrence of oestrogens in pregnancy and pseudopregnancy became apparent thus a placentaloestrogen synthesis in the cat is rather unlikely, also because the oestrogen increase during the last 20 days of pregnancy did not exceed the concentrations determined in oestrus. The differences in the concentration of progesterone in the pregnant and the pseudopregnant group was highly significant (p < 0.0001). Relaxin could only be detected in pregnant cats from day 25 of pregnancy up to parturition. These results confirm earlier data and indicate that endocrine regulation of pregnancy and pseudopregnancy in the Norwegian Forest Cat is not different to that of other domestic cats.
Keywords: Katze; Hormone; Trächtigkeit; Östrogene; Progesteron; ddc:630